Satellite orbit estimation using earth magnetic field measurements - Filipski, Mohammad Nizam; Varatharajoo, Renuganth (Federation of Engineering Institutions of Islamic Countries, 2006)
This paper presents the design of an estimation algorithm for the determination of a low-Earth satellite orbit based only on the measurements of the Earth magnetic field. The algorithm is based on the extended Kalman filter (EKF) and the measure of the magnitude of the magnetic field, which provides an estimation method independent of the satellite attitude. The satellite orbit is described with a state vector formed by the classical Keplerian orbital elements. The simulation test resulted in an accurate estimation of the state vector components and yielded only a few kilometres error on the satellite position. The effect of the variation of the orbit inclination and eccentricity on the filter performances was also investigated.